Measuring Meaningful English Learning Through Video Production: An Instrument Development Report - I Gusti Ngurah Agung Wijaya Mahardika; Ni Komang Arie Suwastini (Universitas Pendidikan Ganesha, 2023)
Students’ low motivation in learning English as a foreign language is an age-old problem for English teachers. To overcome this problem teacher must design and present the learning process in such way which minimize students’ fear and anxiety. One of the more interesting ways to teach English is to use videos in class. The present study aims at developing an instrument to measure students’ perception of the meaningfulness of English learning using video production. This instrument is developed to facilitate the measurement of students’ perception of the meaningfulness of English learning using video. The construct used as the basis of the instrument development is the Meaningful Learning using digital media and video proposed by Paivi Karppinen. The instrument is developed using Borg’s seven steps instrument development process which includes defining the construct to be measured, defining the target population, reviewing related test, developing prototypes (blueprint and test items), evaluating the prototype, revising the instrument, and collecting data on the validity and reliability of the instrument. The final product consists of 23 items, measuring the 6 sub-constructs with Cronbach’s Alpha Value and the Cronbach’s Alpha Based on Standardized items values of .0903 and 0.932 respectively.